ANPEd and intellectual production: a mapping of scientific production concerning indigenous school education (Olhar de Professor, 2023)
This article presents the results of an investigation conducted into intellectual production concerning indigenous school education at national events of the National Association for Postgraduation and Research in Education (ANPEd) in all its working groups in the period from 2007 to 2017, with a specific focus on an analysis of questions considered, methodological processes adopted and the institutions that developed these studies. Our premise was that school education is one of the principal concerns connected to the struggle of indigenous peoples to guarantee their rights, which were achieved with much difficulty in 1988 in the Federal Constitution. An examination of the material collected reveals that research into indigenous school education is still in its early stages, representing in the period from 2007 to 2017 merely 1% of the material relating to the debate around this thematic area.
Keywords: ANPEd.; Indigenous School Education.; Educational Policies.